Tantangan Penanaman Karakter Rasa Cinta Tanah Air di Sekolah Dasar - Suhirda Reski; Ronald Fransyaigu; Sahudra Muhammad Tengku (Journal of Civic Education, 2022)
This research aims to describe what are the challenges of how the internalization the values of love for motherland in the lower grades in elementary school. The background of this study is the phenomenon of decadence of the love for motherland character in Class III.A SDN 2 Kebun Lama, Langsa, Aceh. This research presents a portrait of school policies and how teachers cultivate the love for motherland character in children's attitudes. This research is using a qualitative descriptive approach. Informants were determined by purposive sampling techniques, namely the principal, class teacher, school guard, and students. Data were collected through observation supplemented by interviews and documentation studies. Then the data is tested using triangulation techniques, that is, the data is tested on the same source but with different techniques. The same and different data were found, so the data were tested on different sources. The data were analyzed by Miles and Huberman namely data reduction, data presentation, and conclusion. The findings of this research are the love for motherland characters in Class III.A SDN Kebun Lama, Langsa has been implemented. However, the results have not been seen optimally as can be seen in student activities at school. Then the implementation of the love for motherland character is also hampered due to the Covid-19 pandemic.